Fiqh Rules About Belief and Doubt - Ishan Azis (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
Confidence can be interpreted as a certainty or a strong prejudice against something that is done, and doubts are merely doubts about whether the prejudice is as strong or is there something stronger. Basic Principles about اليَقِيْنُ لاَ يُزَالُ بِالِشَّكِّ . As we know, the fiqh rules have different scopes and scopes, from the broad scope and the most coverage to the fiqh rules which have a narrow scope and little coverage. In addition, Allah SWT does not want to make His people feel difficult, even Allah SWT wants convenience. As in the hadith it is said that الدِيْنُ يُسْرٌ means that the religion of Islam is easy, so with this basic rule it has included how Allah sent down Islamic law for all human beings without any burdensome elements in its implementation.